The contents of labile sulfides in the bottom sediments of the central part of the Sea of Azov: Impact on benthic communities. - Sorokin, Yury I; Burkatskii, O N (PANGAEA, 2007)
At 17 stations in the central part of the Sea of Azov contents of labile (acid-soluble) sulfides were determined in the upper layer (0-3 cm) of bottom sediments. At 14 of these stations contents of sulfides exceeded 300 mg S/l of wet sediment; at seven stations contents of sulfides varied from 420 to 720 mg S/l of wet sediment, or 0.1-0.2% of dry weight. At other three stations, where neutral matter such as shells and sand prevailed in samples, contents of sulfides varied from 80 to 110 mg S/l of wet sediment. At these stations high density and species diversity of benthic fauna was retained. At other stations with labile sulfide contents over 200-300 mg S/l benthos biomass decreased by one or two orders of magnitude. At most of them it was less than 3 g/m**2 and small gastropod Hydrobia tolerant to sulfides dominated. Obtained data show that in the central part of the Sea of Azov reduced sediments with high contents of labile sulfides migrate towards the bottom surface, which conforms to high intensity of hydrogen sulfide formation process caused by bacterial sulfate reduction. The study considers environmental effects of sulfide contamination in the upper layer of bottom sediments in the Sea of Azov as a key factor causing recurrent hypoxy in the near-bottom layers of water, suffocation occurrence, and progressive depletion of benthic and pelagic fauna.
Contents of labile sulfides in the upper layer bottom sediments and parameters of zoobethos density and composition in the central part of the Sea of Azov
Keywords: Archive of Ocean Data; ARCOD; Benthic biomass, wet weight; DEPTH, sediment/rock; Grab; GRAB; Iodometric chemical method; Percentage; Sea of Azov; Sediment type; SoA-03-106; SoA-03-119; SoA-03-131; SoA-03-15; SoA-03-21; SoA-03-28; SoA-03-36; SoA-03-50; SoA-03-60; SoA-03-67; SoA-03-86; SoA-03-87; SoA-03-89; SoA-03-9; SoA-03-96; SoA-03-99; Species; Sulfur bound in sulfide; Sulfur in sulfide; Zoobenthos, biomass